Exploring the Role of Seating Layouts in Enhancing Elementary Students’ Learning Motivation: Evidence from a Controlled Study - Haya Haya (AL-ISHLAH: Jurnal Pendidikan, 2025)
Classroom seating arrangements have long been considered influential in shaping students’ learning experiences, particularly in terms of motivation. This study investigates how seating positions impact students' learning motivation and explores the associated dynamics of social interaction within the classroom setting. A quantitative quasi-experimental design (Nonequivalent Control Group Design) was employed. The study involved 80 fourth-grade students from classes 4A and 4B, selected using a saturated nonprobability sampling technique. Data were gathered through the Motivated Strategies for Learning Questionnaire (MSLQ) and the Classroom Seating Rating Scale for Students (CSRS-S). Data analysis included validity, normality, and linearity tests, followed by hypothesis testing using simple regression. Findings indicated that students seated in the front and middle rows exhibited significantly higher motivation levels than those in the back rows. Contributing factors included increased teacher interaction, stronger peer support, and fewer environmental distractions. Additionally, group seating arrangements were more effective in enhancing motivation compared to individual seating. The results suggest that both seating position and arrangement significantly influence learning motivation. Classroom designs that promote interaction and reduce distractions can positively affect student engagement and motivation. Seating configurations that encourage proximity to the teacher and social interaction, such as group seating in the front or middle rows, enhance students’ motivation. These findings have practical implications for optimizing classroom layouts to foster a more engaging learning environment.